2022
DOI: 10.1186/s43141-022-00309-4
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodological optimization of l-asparaginase production from the medicinal plant endophyte Acinetobacter baumannii ZAS1

Abstract: Background This study targets the enhanced production of l-asparaginase, an antitumor enzyme by Acinetobacter baumannii ZAS1. This organism is an endophyte isolated from the medicinal plant Annona muricata. Plackett–Burman design (PBD) and central composite design (CCD) were used for statistical optimization of media components. Results The organism exhibited 18.85 ± 0.2 U/mL enzyme activities in unoptimized media. Eight variables: l-asparagine, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, a significant difference in the range of L-asparaginase production under varying conditions (runs) suggests the influence of physicochemical parameters on enzyme production. Sharma and Satyanarayana (2011) successfully used statistical optimization to enhance the production of acidic amylase from Bacillus acidicola PB analysis showed the influence of media components and physical parameters on Lasparaginase production from Acinetobacter baumannii ZAS1 (Abhini et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant difference in the range of L-asparaginase production under varying conditions (runs) suggests the influence of physicochemical parameters on enzyme production. Sharma and Satyanarayana (2011) successfully used statistical optimization to enhance the production of acidic amylase from Bacillus acidicola PB analysis showed the influence of media components and physical parameters on Lasparaginase production from Acinetobacter baumannii ZAS1 (Abhini et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2022) showed that the antifungal metabolites production was significantly improved with the addition of soluble starch in S. alfalfae [70]. Carbon sources are essential components not only in constructing cellular materials but also when utilized as energy sources [71]. Nitrogen, on the other hand, is crucial for nucleic acid and protein production, which are the raw materials that create cellular metabolites [72].…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sources are essential components in constructing cellular materials and are also used as energy sources [35]. Nitrogen is an important element for nucleic acid and protein, which are the raw materials synthesized by microorganisms to create cellular metabolites [36].…”
Section: Discussionmentioning
confidence: 99%
“…Minerals such as K + , Ca 2+ , Na + and Mg 2+ have been known to play a crucial role in the metabolic process of all microorganisms, as it is essential for the formation of cell mass and acts as a cofactor for many biosynthetic enzymes to catalyze the necessary reactions [35]. Zhu et al (2007) made an effort to ameliorate the production of avilamycin using Streptomyces viridochromogenes Tu57-1 and by adopting BBD in which they found a maximum production of 88.33 mg/L (2.80-fold increase) in the optimized medium with the ingredients such as MgSO 4 •7H 2 O 0.37 g/L, CaCl 2 •2H 2 O 0.39 g/L, soybean flour 21.97 g/L and soluble starch 37.22 g/L [41].…”
Section: Discussionmentioning
confidence: 99%